COMPARATIVE STUDY OF HATCHABILITY AND FERTILITY RATE AMONG LOCAL QUAILS - & Al-Barzinji, Ahmed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
An experiment was conducted to evaluate fertility, hatchability, egg weight and egg production traits from three different lines of local quails. A total number of 945 eggs (334, 321 and 290 for desert, brown and white, respectively), from 20 weeks of age were used in the study. White quail significantly (P≤0.05) produce higher egg weight (12.79 ± 0.08 g), chicks' weight (8.89± 0.02 g), percentage of mortality (2.34 ± 0.70 %) and Hen-day egg production (79.33 ± 0.98 %) comparing with other local quails. While local brown quail have significantly (P≤0.05) higher percentages of fertility and hatchability which averaged 79.11 and 86.80%, respectively. The higher total number of egg and low mortality percentage (0.93 ± 0.40 %) were recorded for desert local quail. The significant positive correlation (P≤0.001) were observed between the eggs weight and chick weight, fertility and hatchability,  eggs weight and hatchability were arrived 0.276, 0.180 and 0.872, respectively. But non significant negative correlation recorded between chick weight with both of fertility and hatchability. These results show that there are good among of variance in performance production among different local quails, its means the selection process among these types of bird can play major role to speed up and increasing the economical traits of local quail in Iraqi Kurdistan region.